Analisis Kinerja Perusahaan dengan Pendekatan Balanced Scorecard - Abdul Suhada; Endang Hendrayanti (Fakultas Ekonomi Universitas Islam 45, 2019)
The aim of this study was to improve company performance using a balance score card (BSC) with support from the customer's perspective.Internal business perspective and learning and growth perspective. The data source used is primary data and secondary data. The data is processed by measuring the achievement of the weighted performance that has been set and compared with the realization of its performance. Based on the results of BSC calculations, it is known that the performance of PT Ju Won from the customer's perspective is obtained from the customer retention value of 83.3%, meaning that the company has succeeded in retaining old customers with very good value. In the perspective of internal business processes, the value of 75% manufacturing cycle efficiency based on this value is quite good because it exceeds 50%.From the learning and growth perspective, it is found that employee turnover is 7.2%, which means that employee turnover is quite high, employee turnover value is high, it will add costs for recruitment, training costs and the adaptation process.